The PENGEMBANGAN BUKU AJAR BERBASIS PROBLEM SOLVING METHOD UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR - Wedyawati, Nelly (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2020)
The present research aimed to describe the stages of developing science textbooks based on problem solving methods to improve students’ learning outcomes. Data collection were questionnaires (expert assessment), teacher questionnaires, student questionnaires, learning achievement tests, and documentation. The data analysis covered the research preparation data, the expert assessment data, the teacher response data, the students’ response data, and the learning outcomes. The media validation score on the product was 80.33 and the material validation score was 89.25, the product was declared eligible to be applied. Student learning outcomes improved, the score on the limited scale try-out was 100, the score on the wide scale try-out each was 100. The conclusion of this study is the development of science textbooks based on problem solving method to improve the learning outcomes of Year-3 students elementary schools declared feasible, effectively improved learning outcomes, and accepted by book users. Research recommendation is that this developed book based onproblem solving method be published. Keywords: Textbook, Problem Solving, Method, Learning Outcome, Elementary School